2020
DOI: 10.1016/j.anai.2019.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes and endotypes in eosinophilic esophagitis

Abstract: Eosinophilic esophagitis (EoE) shares many features with other atopic diseases such as asthma, including heterogeneity in its presentation, natural history, and response to treatment. Clinical and molecular evidence suggests that different eosinophilic esophagitis patient phenotypes and endotypes exist. Phenotypic variations in EoE include the age of onset, degree of atopic comorbidity, response to different forms of therapy, and disease severity, among others. Biomarkers that may provide insight into the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 77 publications
0
42
0
1
Order By: Relevance
“…The potential for endotypes to transform classification and treatment has been demonstrated in a number of domains, including cancer, asthma, and multiple sclerosis. Endotypes are a fundamental principle in personalized (precision) medicine because they may form the foundation for prognostic enrichment, in which participants are selected on the basis of the likelihood that they will experience a specific outcome, and for predictive enrichment, in which patients are selected on the basis of the likelihood that they will respond to an intervention [11][12][13][14][15][16][17][18][19][20].…”
Section: Defining Endotypes/phenotypesmentioning
confidence: 99%
“…The potential for endotypes to transform classification and treatment has been demonstrated in a number of domains, including cancer, asthma, and multiple sclerosis. Endotypes are a fundamental principle in personalized (precision) medicine because they may form the foundation for prognostic enrichment, in which participants are selected on the basis of the likelihood that they will experience a specific outcome, and for predictive enrichment, in which patients are selected on the basis of the likelihood that they will respond to an intervention [11][12][13][14][15][16][17][18][19][20].…”
Section: Defining Endotypes/phenotypesmentioning
confidence: 99%
“…However, a significant number of EoE patients do not present allergic diseases, suggesting a possible non-atopic phenotype (2). Interestingly, several reports have suggested that EoE may be more frequently associated with some non-allergic disorders, including connective tissue disorders (74), autoimmune diseases (coeliac disease) ( 8), and contradictorily inflammatory bowel diseases (IBD) (8,(75)(76)(77), that are increased in the last decades, especially in Western countries (8).…”
Section: Diseases Of Modern Life and Phenotypes Of Eoementioning
confidence: 99%
“…EoE is a chronic, antigen-mediated, inflammatory disease of the esophagus characterized by symptoms due to esophageal inflammation, dysmotility, and fibrosis (1,2). EoE occurs in children and adults, and symptoms are often non-specific and depending on the age of onset (1,2).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations